تطوير أدوات تقويم تعليم اللّغة العربيّة على أساس التّكنولوجيا - Erma Febriani; Falahun Ni'am (UIN Fatmawati Sukarno Bengkulu, 2022)
The researcher was interested in developing evaluation tools based on technology. The objectives of the research are: Developing assessment tools for learning Arabic based on technological developments. The type of research used in this research is research and development. The product developed in this study is assessment tools for learning Arabic based on technological developments. The development procedure consists of five steps, namely: 1) analysis,2) the design , 3) Development ,4) implementation, 5) Calendar. The data collection tool used was a semi-closed questionnaire. Data processing is done after obtaining data from the results of the experiment. The data is then analyzed using the percentage formula. The results of the data analysis showed that the percentage of candidate individual user experiences was88.33% and small group users90.25٪ and field experiments91.41%